CREATION AND RESEARCH OF SPECIAL CLOTHING FOR EMPLOYEES OF THE COTTON AND TEXTILE CLUSTER, THE OPERATIONAL CHARACTERISTICS OF WHICH ARE OPTIMIZED (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article explores the development and research of specialized clothing for employees working in the Cotton and Textile Cluster. The objective is to optimize the operational characteristics of this clothing to enhance employee performance, safety, and comfort. This innovative approach not only benefits workers but also contributes to the overall productivity and sustainability of the industry.